Trends in kidney failure and kidney replacement therapy in people with diabetes in Hong Kong, 2002-2015: A retrospective cohort study - Hongjiang Wu, PhD; Eric S.H. Lau, PhD; Aimin Yang, PhD; Cheuk-Chun Szeto, MD; Ronald C.W. Ma, FRCP; Alice P.S. Kong, MD; Elaine Chow, PhD; Wing-Yee So, MD; Juliana C.N. Chan, MD; Andrea O.Y. Luk, MD (Elsevier, 2021)
Background: There are limited population-wide trend data on kidney failure and kidney replacement therapy (KRT) in people with diabetes. We conducted a retrospective cohort study to report incidence trends of kidney failure and KRT and related mortality in people with diabetes in Hong Kong between 2002 and 2015. Methods: We used territory-wide electronic medical records including laboratory, diagnostic and procedural data to identify people with kidney failure and KRT. We used Joinpoint regression models to estimate the average annual percent change (AAPC) of kidney failure and KRT incidence for entire study period, and annual percent change (APC) for each linear trend segment, along with 1-year and 5-year mortality rates. Findings: During 4.9 million person-years of follow-up of 712,222 people with diabetes, 31,425 developed kidney failure, among whom 23.0% (n=7,233) received KRT. The incidence of kidney failure declined by 46.8% from 2002 to 2007 (APC: -11.6, 95% CI: -16.3, -6.7), then flattened from 2007 to 2015 (APC: -0.9, 95% CI: -3.1, 1.3). The incidence of KRT remained constant (AAPC: -1.6, 95% CI: -4.4, 1.2). The 1-year mortality rates declined statistically significantly after both kidney failure and KRT. The 5-year mortality rates declined after kidney failure but the decline was not statistically significant after KRT. Interpretation: The findings of our study highlight the importance of developing new strategies to prevent a looming epidemic of kidney failure in people with diabetes in Hong Kong. Funding: Asia Diabetes Foundation